2013
DOI: 10.1371/journal.pone.0081318
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Fatty Acid-Binding Protein Family and Metabolic Phenotype in the General Population

Abstract: ObjectiveFatty acid-binding proteins (FABPs) are a family of 14-15-kDa proteins, and some FABPs have been to be used as biomarkers of tissue injury by leak from cells. However, recent studies have shown that FABPs can be secreted from cells into circulation. Here we examined determinants and roles of circulating FABPs in a general population.MethodsFrom the database of the Tanno-Sobetsu Study, a study with a population-based cohort design, data in 2011 for 296 subjects on no medication were retrieved, and FABP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
133
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 40 publications
14
133
6
2
Order By: Relevance
“…For example, intrarenal CD36 has been identified as a novel mediator in renal diseases associated with proteinuria and renal dysfunction (35). The elevated level of serum/plasma/urinary Fabp4 is considered a predictor or biomarker for renal dysfunction in diabetes and cardiovascular diseases (23)(24)(25)(26)(27). Hence, we further hypothesized that these affected IUGR offspring fed with HFD would develop metabolic perturbations and kidney injury in adulthood that might be associated with alterations of both renal CD36 and Fabp4 gene expression.…”
Section: Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, intrarenal CD36 has been identified as a novel mediator in renal diseases associated with proteinuria and renal dysfunction (35). The elevated level of serum/plasma/urinary Fabp4 is considered a predictor or biomarker for renal dysfunction in diabetes and cardiovascular diseases (23)(24)(25)(26)(27). Hence, we further hypothesized that these affected IUGR offspring fed with HFD would develop metabolic perturbations and kidney injury in adulthood that might be associated with alterations of both renal CD36 and Fabp4 gene expression.…”
Section: Articlesmentioning
confidence: 99%
“…Emerging evidence suggested that CD36 (19)(20)(21)(22) and Fabp4 (23)(24)(25)(26)(27) are highly implicated in the pathogenesis of HFDinduced cell damage. For example, intrarenal CD36 has been identified as a novel mediator in renal diseases associated with proteinuria and renal dysfunction (35).…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…A full colour version of this figure is available at http:// dx.doi.org/10.1530/JOE-17-0031. correlated with adiposity (Xu et al 2006, Ishimura et al 2013. Despite its lack of an N-terminal secretory signal sequence (Furuhashi & Hotamisligil 2008), FABP4 has been reported to be released from adipocytes through additional mechanisms (Coe et al 1999, Scheja et al 1999, Shen et al 1999, Mita et al 2015 and acts as an adipokine in several organs, including the heart (Fig.…”
Section: Figurementioning
confidence: 99%
“…It is possible that the level of FABP4 secreted from endothelial cells is sufficient for causing significant effects on nearby vascular endothelial cells and smooth muscle cells, leading to an inflammatory response, proliferation, and migration from the media into the intima. The circulating level of FABP4 is ≈20 ng/mL (1 nmol/L) in humans 19. Since autocrine and paracrine actions of the secreted FABP4 derived from regenerated endothelial cells were focused on in the present study, the concentration of recombinant FABP4 used (≈200 nmol/L) seems to be reasonable and physiological in the local area.…”
Section: Discussionmentioning
confidence: 81%